Last laugh - Alexander, K. R. 1986- (New York, NY Scholastic Inc., 2024)
"What's scarier than a collection of clown dolls in a secret locked room? How about ... those clown dolls coming to life. And hunting you down"--$Provided by publisher.
Ages 8-12